A genetic variant of miR‐335 binding site in the ERBB4 3′‐UTR is associated with prognosis of ovary cancer. Issue 7 (6th April 2018) - Wei, Ping; Li, Ling; Zhang, Zhihu; Zhang, Wei; Liu, Ming; Sheng, Xiugui
ABSTRACT: Ovarian cancer is one of the leading gynecologic malignancies globally, the 5‐year survival rate for patients with advanced stage ovarian cancer is very low. Our objective was to test the hypothesis that miR‐335 was associated with the survival of patients with ovarian cancer. Bioinformatics tools and luciferase report assay were used to select the target of miR‐335, and real‐time PCR was used to detect the expression of miR‐335 and ERBB4 in different genotype groups. Finally, Cox regression and Kaplan‐Meier analyses were used to assess the relationship of ERBB4 genotype and survival of ovary cancer. Firstly, individuals carried ERBB4 rs186724 GG genotype had poorer overall survival compared with those carried CC/CT genotypes in ovarian cancer, while the participants with rs1836724 GA genotype had the same overall survival with that in participants with rs1836724 AA genotype in accordance with the result of Cox regression and Kaplan‐Meier analyses. Then according to result of the in‐silicon analysis, ERBB4 was the target of miR‐335, and rs1836724 was located on 3′UTR of ERBB4, the binding site of miR‐335, and miR‐335 inhibited the expression of ERBB4 and this regulation was more suppressed when the G allele replaced by the variant A allele. Finally, miR‐335 was similar among GG, GA, and AA groups, and ERBB4 level was higher in GG group. Finally, malignant grade is apparently higher in GG group than the other group. The data indicated that the ERBB4 rs1836724 polymorphism was associated with the survival of ovarian cancer. Abstract : The data indicated that the ERBB4 rs1836724 polymorphism was associated with the prognosis of ovarian cancer.